2020
DOI: 10.3928/01913913-20200506-01
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Corneal Structural Development During Childhood Characterized by Ultrasound Biomicroscopy

Abstract: Purpose: To quantitatively describe the structural corneal changes from infancy to early adulthood using ultrasound biomicroscopy. Methods: In this prospective study, 168 ultrasound biomicroscopy images were obtained from 24 healthy eyes of 24 patients who consented and enrolled in the Pediatric Anterior Segment Imaging Innovation Study. Their ages ranged from birth to 26 years. An established ultrasound biomicroscopy imaging protocol including seven vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…The average measurement from the six images was used for analysis. A total of 21 parameters (Table 2) were measured based on a previously defined protocol, 13 including measurements from the central and posterior cornea, anterior chamber, trabecular iris angles, and sclera, using the angle-to-angle distance (AA-D) and scleral spur (SS) as landmarks. In this study, additional parameters including distance from the scleral spur to the mid-iris insertion and anterior ciliary body insertion (Fig.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average measurement from the six images was used for analysis. A total of 21 parameters (Table 2) were measured based on a previously defined protocol, 13 including measurements from the central and posterior cornea, anterior chamber, trabecular iris angles, and sclera, using the angle-to-angle distance (AA-D) and scleral spur (SS) as landmarks. In this study, additional parameters including distance from the scleral spur to the mid-iris insertion and anterior ciliary body insertion (Fig.…”
Section: Subjectsmentioning
confidence: 99%
“…All images included in this study were obtained by the same examiner, a trained ophthalmologist who obtained two axial and four longitudinal images per eye in predefined locations and probe positions according to previously published protocols. 12,13 Ultrasound biomicroscopy image analysis was performed using ImageJ software. Masked measurements for each image were performed by two different expert observers, and their measurements were averaged to determine each parameter measurement value.…”
Section: Subjectsmentioning
confidence: 99%
“…Other pediatric corneal diseases evaluated using UBM includes keratoconus (acute hydrops [60,61], and intrastromal ring implantation [62]), and deep anterior lamellar keratoplasty (DALK) outcomes and indications [63]. Normal corneal growth evaluation using UBM identified and quantified structures with statistically significant differences in younger eyes, and provided baseline reference values for comparison in future studies [64].…”
Section: Corneamentioning
confidence: 99%
“…Three of these studies focused on premature infants [79][80][81], and four focused on anterior segment changes concurrent with accommodation and dilation [65,[82][83][84]. These studies provide useful normative data [64,[85][86][87], and emphasize the importance of controlling for age and environmental factors during UBM imaging.…”
Section: The Structural Anatomy Of the Pediatric Eyementioning
confidence: 99%
“…4 Previous case-control studies have shown UBM findings in various anatomic locations, including the ciliary body, iridocorneal angle, and iris, are associated with primary congenital glaucoma. [5][6][7][8][9][10] Although the prognostic and diagnostic impact of these features are still under investigation, there is a current need to produce methods for successful automatic characterization of multiple anatomic locations in UBM to aid these efforts.…”
Section: Introductionmentioning
confidence: 99%